A genealogy of hacking. (October 2017) - Jordan, Tim
Hacking is now a widely discussed and known phenomenon, but remains difficult to define and empirically identify because it has come to refer to many different, sometimes incompatible, material practices. This article proposes genealogy as a framework for understanding hacking by briefly revisiting Foucault's concept of genealogy and interpreting its perspectival stance through the feminist materialist concept of the situated observer. Using genealogy as a theoretical frame, a history of hacking will be proposed in four phases. The first phase is the 'prehistory' of hacking in which four core practices were developed. The second phase is the 'golden age of cracking' in which hacking becomes a self-conscious identity and community and is for many identified with breaking into computers, even while non-cracking practices such as free software mature. The third phase sees hacking divide into a number of new practices even while old practices continue, including the rise of serious cybercrime, hacktivism, the division of Open Source and Free Software and hacking as an ethic of business and work. The final phase sees broad consciousness of state-sponsored hacking, the re-rise of hardware hacking in maker labs and hack spaces and the diffusion of hacking into a broad 'clever' practice. In conclusion, it will be argued that hacking consists across all the practices surveyed of an interrogation of the rationality of information technocultures enacted by each hacker practice situating itself within a particular technoculture and then using that technoculture to change itself, both in changing potential actions that can be taken and changing the nature of the technoculture itself.